2014
DOI: 10.3109/00207454.2014.896913
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of morphine analgesia and prevention of morphine tolerance by downregulation of β-arrestin 2 with antigene RNAs in mice

Abstract: β-arrestin 2, a regulatory molecule of G protein-coupled receptor, has been proved to play an important role in regulating functions of mu opioid receptor. Changes of β-arrestin 2 expression might affect the function of mu opioid receptors and the effect of its agonists. In this study, antigene RNAs (agRNAs), which could selectively target gene transcription start sites and potently inhibit gene expression, were used to downregulate the expression of β-arrestin 2 to investigate its effects on morphine analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Constitutive deletion of barr2 resulted in viable mice on an S129/C57BL/6 background, and initial experiments with morphine revealed both enhanced potency and extended duration of action in the hot plate assay, a measure of supraspinally mediated antinociception (8)(9)(10), and in the warm water tail immersion assay, a measure of spinal reflex to nociceptive stimuli (11,12). These behavioral results have also been observed in mice treated intracerebroventricularly with via antigene RNA inhibition of barr2 (13). Mice injected with short interfering RNA (siRNA) to barr2 but not to barr1 into the periaqueductal gray showed enhanced and prolonged antinociception, while overexpression of barr2 but not of barr1 inhibited morphine-induced antinociception in the hot plate test (14).…”
Section: Genetically Modified Mouse Models As Indicators Of Physiologmentioning
confidence: 79%
“…Constitutive deletion of barr2 resulted in viable mice on an S129/C57BL/6 background, and initial experiments with morphine revealed both enhanced potency and extended duration of action in the hot plate assay, a measure of supraspinally mediated antinociception (8)(9)(10), and in the warm water tail immersion assay, a measure of spinal reflex to nociceptive stimuli (11,12). These behavioral results have also been observed in mice treated intracerebroventricularly with via antigene RNA inhibition of barr2 (13). Mice injected with short interfering RNA (siRNA) to barr2 but not to barr1 into the periaqueductal gray showed enhanced and prolonged antinociception, while overexpression of barr2 but not of barr1 inhibited morphine-induced antinociception in the hot plate test (14).…”
Section: Genetically Modified Mouse Models As Indicators Of Physiologmentioning
confidence: 79%
“…As a G protein-coupled receptor (GPCR), the MOR also interacts with βarrestins, scaffolding proteins that serve to regulate or facilitate subsequent GPCR signaling. In studies spanning more than a decade, researchers have shown that the interaction between MOR and βarrestin2 may drive many of the unwanted side effects of MOR activation (Bohn et al, 2000; Bohn et al, 1999; Bu et al, 2015; Li et al, 2009; Raehal, 2011; Raehal and Bohn, 2005). βArrestin2-KO mice, for example, display enhanced and prolonged morphine-induced antinociception yet are protected from morphine-induced respiratory suppression (Bohn et al, 1999; Raehal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the knockdown or deletion of barrestin2 has been shown to attenuate morphine tolerance in rodent models (Bu et al, 2015;Li et al, 2009;Yang et al, 2011). We found that while barrestin2knockout (KO) mice did not become tolerant in the hot plate test, they did become tolerant in the warm water tail immersion assay (Bohn et al, 2002).…”
Section: Introductionmentioning
confidence: 87%